Dług publiczny samorządu terytorialnego - Sawicka, Krystyna (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
In the article the public debt of local self-governance is elucidated. The conclusion, that the debt acquiring is the consequence of the local self-governance development and is aimed at the improvement of the quality and accessibility of the state services. On the basis of the analysis of the scientific legal literature, the author makes her own conclusions with regard of the issue of the research.
Keywords: dług publiczny samorządu terytorialnego; samorząd terytorialny; poprawa jakości i dostępności usług państwa